1995
DOI: 10.1002/app.1995.070580501
|View full text |Cite
|
Sign up to set email alerts
|

Thermolysis of polystyrene

Abstract: Styrene was r EK:overed trom polystyrene (molecular weight of 138 OO~) by thermolysis in a nitrog,en atmosphem .at templ3ratures between 368°C and 407°C. The' results wc~n9 inaepElndent of thE~ initial weight of polystyrene which was varied between ~30 and 480 grar~s. Up to 70% of the polystyrene was converted to styrene. The styrene yield increased with temp€;'rature. At higher temperatures, the residue left il1 thE! reactor Gonsisted mainly of styrene monomer, dimer and trimer (MW of 190). The maximum rate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
14
1
1
Order By: Relevance
“…Bockhorn defined degree of conversion as the mass of gas products evolved at times 't' divided by the total mass of evolved gas products when the sample was pyrolyzed completely. Simard [20] condensed and measured the volatiles and reported kinetic data in terms of product yield, which was defined as the ratio of the weight of condensate to the weight of initial polystyrene. Liu et al's [18] technique involved pyrolysis of the sample several times sequentially for the same length of time until no gaseous products are evolved from the sample.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Bockhorn defined degree of conversion as the mass of gas products evolved at times 't' divided by the total mass of evolved gas products when the sample was pyrolyzed completely. Simard [20] condensed and measured the volatiles and reported kinetic data in terms of product yield, which was defined as the ratio of the weight of condensate to the weight of initial polystyrene. Liu et al's [18] technique involved pyrolysis of the sample several times sequentially for the same length of time until no gaseous products are evolved from the sample.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…(22) has the same form with the equations used in other researches' work [20][21][22][23], which implies that using the assumption and continuous distribution kinetics to describe this process is proper and reasonable. Eqs.…”
Section: Theoretical Modelmentioning
confidence: 94%
“…18 Moreover, the activation energy in this study was lower than previously reported thermolysis values, which varied between 133 and 290 kJ/ mol. 15,16 Compared with thermal degradation without solvents, PS degradation in supercritical toluene was in the homogeneous phase, which should have decreased the activation energy.…”
Section: Temperature Dependence Of Ps Degradationmentioning
confidence: 99%
“…It is widely accepted that the kinetics of PS degradation in the range 300-4008C follow the first order. [13][14][15][16] The conversion (c) can be calculated from the following equation:…”
Section: Introductionmentioning
confidence: 99%